The effects of low dose N-acetylcysteine as an additive to cardioplegia in CABG patients - Koksal, H; Rahman, A; Burma, O; Uysal, A; Akar, I; Halefoglu, I; Bayar, MK (Medimond Publishing Co, 2005)
Reactive oxygen species have been shown to contribute to myocardial stress in patients undergoing cardiac surgery. Thirty patients operated due to triple coronary artery disease were enrolled to study as control group (n=15) and study group (n=15). N-Acetylcysteine (NAC) were added to cardioplegic solutions in study group. Hemodynamic measurements were done pre and postoperative periods. Blood samples for malondialdehyde (MDA) and neutrophil counts were obtained from coronary sinus before cardiopulmonary bypass, just before the cross-clamp removed and 30 minutes later. There were no significant difference between groups at hemodynamic parameters. MDA levels and neutrophil percentage were significantly lower in study group than control group at 30 minutes later the cross-clamp removed period (p < 0.05).
6th International Congress on Coronary Artery Disease -- OCT 29-NOV 01, 2005 -- Istanbul, TURKEY
Keywords: Ischemia-Reperfusion Injury; Cardiopulmonary Bypass; Stress; Oxygen